Laparoscopic repair of a bilateral internal inguinal hernia with supravesical hernia – a case report - Kawaguchi, Tsutomu (Int J Surg Case Rep, 2015)
INTRODUCTION: Supravesical hernia is an exceptional subtype of internal inguinal hernia, and it is located between the median umbilical ligament and the medial umbilical ligament. The hernia is classified as two types: internal supravesical hernia and external supravesical hernia. PRESENTATION OF CASE: Herein we report a rare case of external supravesical hernia successfully treated by laparoscopic procedure. The patient who complained right inguinal protrusion and mild frequent urination was diagnosed as right inguinal hernia and potential of left inguinal hernia using computed tomography. He underwent laparoscopic bilateral hernia repair, and intraoperative findings revealed right external supravesical hernia and left internal inguinal hernia. DISCUSSION: Laparoscopic hernia repair may make it possible to avoid overlooking of internal hernia such as supravesical hernia. Moreover it was possible to cover the hernia orifice and dissected layer of the dorsal site of urine bladder using bilateral approach in the current case. CONCLUSION: In conclusions, laparoscopic hernia repair might be a surgical option for supravesical hernia.